FORESIGHT AND THE ROLE OF INNOVATION IN THE DEVELOPMENT OF EDUCATION - K. G. Kassymova; I. Y. Aksarina; A. V. Demchuk; G. A. Stepanova; Y. S. Aksarina; M. A. Bogach; S. N. Brovkina; A. V. Kosov; M. R. Arpentieva; S. K. Dossayeva (Scientific Journal of Pedagogy and Economics, 2019)
Foresight is a system of methods for transforming priorities in education and science, economics and production, social and cultural development. In modern Russia, the foresight of education acts as a means of its collapse: theorists and methodologists of educational foresight, working on behalf of comprador corporations, consistently build a system of priority tasks that not only ignore the domestic experience of education and upbringing, but also destroy it and its ideals. The development and self-realization of the person was replace by the values of selling the person and using it in the most convenient ways for corporations. The purpose of the study is to analyze the problems and prospects of modern education as a theory and practice, which combines the experience of training and educating a person throughout his life in various (subject/professional) fields and situations gained by many generations, communities, cultures, humanity as a whole. The basis of the research is the theoretical analysis and integration of data on various theoretical and practical pedagogical, psychological, sociological and other models of education and the development of education in order to identify problems of the foresight of modern education. The main line of transformations during the transition to a new way of life is no more sophisticated exploitation of man and society as "capital", but the priority of these types of "capital" is in itself.